Amyloid Precursor Protein Is Associated with Aggressive Behavior in Nonluminal Breast Cancers. (14th August 2018) - Tsang, Julia Y.S.; Lee, Michelle A.; Ni, Yun‐Bi; Chan, Siu‐Ki; Cheung, Sai‐Yin; Chan, Wai‐Wa; Lau, Kwok‐Fai; Tse, Gary M.K.
Abstract: Background: β‐amyloid precursor protein (APP), a potential target for Alzheimer's disease treatment, has recently been shown to take part in carcinogenesis. Increased APP promotes migration, survival, and proliferation in breast cancer cell lines. We examined the clinical value of APP in breast cancers. A comprehensive examination of clinicopathological features related to APP expression in a large cohort of breast cancers and the corresponding metastatic lymph nodes was performed. APP expression and its prognostic impact in different breast cancer subtypes were examined. Results: APP was highly expressed in nonluminal breast cancers and correlated with features associated with nonluminal breast cancers (including higher grade, the presence of necrosis, and higher proliferative index, growth factor receptor, and basal marker expression). Multivariate Cox hazard analysis demonstrated that APP was an independent adverse prognostic factor of disease‐free survival (DFS; hazard ratio [HR], 2.090; p = .013; 95% confidence interval [CI], 1.165–3.748) and breast cancer‐specific survival (BCSS; HR, 2.631; p = .002; 95% CI, 1.408–4.915) in the nonluminal group. The independent prognostic impact was also seen in triple negative breast cancers. Interestingly, a higher expression of APP was found in nodal metastasis compared with primary tumor. Such APP upregulation was correlated with further distal metastasis and poorer outcome (DFS: log‐rank, 12.848; p < .001; BCSS: log‐rank, 13.947; p < .001). Conclusion: Our findings provided evidence of oncogenic roles of APP in clinical breast cancers. Patients with positive APP expression, particularly those with APP upregulation in lymph node metastases, may require vigilant monitoring of their disease and more aggressive therapy. Implications for Practice: β‐amyloid precursor protein (APP), a potential target for Alzheimer's disease, has recently been implicated in oncogenesis. Here, evidence of its roles in clinical breast cancers is provided. Positive APP expression was found to be an independent prognostic factor in nonluminal cancers, particularly triple negative breast cancers (TNBCs). Interestingly, a higher APP in nodal metastases was associated with distal metastases. TNBCs are heterogeneous and currently have no available target therapy. APP could have therapeutic potential and be used to define the more aggressive cases in TNBCs. Current prognostic analysis is based on primary tumor. The present data suggest that investigation of nodal metastases could provide additional prognostic value. Abstract : This article assesses the expression of the α‐amyloid precursor protein (APP) in a large series of breast carcinomas and the corresponding metastatic lymph nodes.